(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to identify the level of moral intelligence among female students of the Faculty of Education at Tishreen University, as well as to identify the differences in the views of the sample of students about the level of moral intelligence according to the following variables: (place of residence, specialization), use the descriptive approach. The sample included (276) female students from the College of Education from majors (curricula and teaching methods, child education as a class teacher, and psychological counseling) for the academic year 2022-2023. To achieve the goal of the research, a questionnaire was designed consisting of (51) phrases, distributed over seven domains (emotional representation, conscience, self-control, respect, kindness, tolerance, and justice). The results of the research showed that the level of moral intelligence among female students of the Faculty of Education at Tishreen University was moderate. The results also showed that there was a statistically significant difference between the mean scores of the sample on the moral intelligence scale according to the place of residence variable in favor of city students, and there were no statistically significant differences between the mean scores of the sample on the moral intelligence scale according to the specialization variable. The research presented many proposals, the most important of which are: spreading the culture of moral intelligence in the College of Education, promoting its concepts, and designing programs to develop moral intelligence among university students.